2022
DOI: 10.3390/molecules27072345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cosmetic and Dermatological Properties of Kombucha-Fermented Berry Leaf Extracts Considered to Be By-Products

Abstract: Leaves of Rubus fruticosus L., Vaccinum myrtillus L., Ribes nigrum L. and Fragaria vesca L. are considered agro-waste of the berry industry, but they can be a rich source of valuable bioactive compounds used in cosmetic industry. In this study, kombucha-fermented and non-fermented extracts were compared in terms of chemical composition and biological activity. Polyphenol compounds were identified by HPLC/DAD/ESI-MS. The antioxidant potential was analyzed by evaluating the scavenging of intracellular free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 79 publications
2
14
0
Order By: Relevance
“…For example, for F. vesca , the gallic acid content of F20 is about 12 times higher than that of the extract. An earlier paper published by Ziemlewska et al [ 5 ] determined the content of the biologically active compounds that are present in berry leaf extracts, which are often considered to be agro-waste. Compared to berry fruits, leaf extracts and their kombucha ferments at the same tested concentration are characterized by a higher content of polyphenols, which also translates to the antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for F. vesca , the gallic acid content of F20 is about 12 times higher than that of the extract. An earlier paper published by Ziemlewska et al [ 5 ] determined the content of the biologically active compounds that are present in berry leaf extracts, which are often considered to be agro-waste. Compared to berry fruits, leaf extracts and their kombucha ferments at the same tested concentration are characterized by a higher content of polyphenols, which also translates to the antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The cosmetics industry is increasingly turning to natural plant substrates that were previously considered to be waste products, such as leaves or fruit seeds. Subjecting them to a fermentation process has yielded surprising discoveries of properties that are quite different from those known in fruits [ 5 ]. The same strategy is also used in the production of biosurfactants, which are characterized by higher activity and stability compared to the surfactants that are obtained synthetically.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested the potential use of strawberries in cosmetic and pharmaceutical topical products, providing possible antioxidant, photoprotective, and anti-aging activities [ 63 , 64 , 65 , 66 , 67 ]. Hence, the bioactivity of the total polyphenol leaf extract was evaluated in terms of cytotoxicity, UV-photoprotection, and wound healing potential in human melanoma cells (SK-MEL-28) and in murine embryo fibroblasts (NIH/3T3).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of intracellular reactive oxygen species (ROS) in the endothelial cells was performed as previously described [ 40 ]. After 24 h of incubation, the medium was removed and replaced with 10 μM H 2 DCFDA (Sigma Aldrich), and the cells were incubated for 45 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%